Improving Legibility of Motor Current Spectrum for Broken Rotor Bars Fault Diagnostics - Asad Bilal; Vaimann Toomas; Kallaste Ants; Rassõlkin Anton; Belahcen Anouar; Iqbal M. Naveed (Electrical, Control and Communication Engineering)
In this paper, the harmonic contribution of the broken rotor bar of an induction machine is investigated using an effective combination of the fast Fourier transform (FFT) and a band stop filter. The winding, spatial, grid fed and fault-based harmonics are investigated. Since the fundamental component is the most powerful component as compared to the other frequencies, it decreases the legibility of spectrum, making logarithmic scale inevitable. It also remains a potential threat of burying the fault representative side band frequencies because of its spectral leakage. In this paper, a band stop Chebyshev filter is used to attenuate the fundamental component, which makes the spectrum clearer and easier to understand even on the linear scale. Its good transition band and low passband ripples make it suitable for attenuating the main supply frequency with low impact on the neighbouring side band frequencies. To study the impact of fault on magnetic flux distribution, simulation is done using finite element method with good number of mesh elements and very small step size. The line current is calculated and frequency spectrum is investigated to segregate the spatial and fault frequencies using the proposed technique. The results are further validated by implementing the algorithm on the data measured in the laboratory environment including the grid fed harmonics.